The Crucial Role of Safety in Carbon Capture and Storage: Addressing Knowledge Gaps for a Sustainable Future - Federica Tamburini; Francesco Zanobetti; Sarah Bonvicini; Valerio Cozzani (Chemical Engineering Transactions)
Global warming, driven largely by rising carbon dioxide (CO2) emissions from human activities, continues to pose a critical global challenge, impacting ecosystems, economies, and public health. Carbon Capture and Storage (CCS) has emerged as a promising strategy for reducing emissions, particularly during the ongoing energy transition when fossil fuels remain a primary energy source. However, the effectiveness and public acceptance of CCS are hampered by safety concerns throughout its value chain, especially due to the peculiar thermodynamic properties of CO2. This paper addresses such safety concerns reviewing existing literature on risk assessment and safety evaluation models for CCS technology, identifying key knowledge gaps across all stages of the CCS value chain. Then, to bridge these gaps, a twofold approach is proposed: i) the study compiles a comprehensive baseline of reference data for the safety assessment of CCS systems; ii) inherent safety principles are applied to a real-world-like CCS case study, using consequence modelling to assess specific hazard indexes. By combining the theoretical review with practical applications, the paper emphasizes the importance of integrating safety into CCS design and operations and provides data to support safety enhancement in future CCS projects.